Copper Clusters: An Effective Antibacterial for Eradicating Multidrug‐Resistant Bacterial Infection In Vitro and In Vivo. (29th January 2021) - Zhang, Xiangchun; Zhang, Zhichao; Shu, Qingming; Xu, Chao; Zheng, Qinqin; Guo, Zhao; Wang, Chen; Hao, Zhenxia; Liu, Xin; Wang, Guoqing; Yan, Wangjun; Chen, Hongping; et al.
Abstract: Infections caused by multidrug‐resistant (MDR) bacteria pose a threat to human health worldwide, making new effective antibacterial agents urgently desired. To date, it is still a great challenge to develop new antibiotics for MDR bacteria with clear antibacterial mechanisms. Herein, a novel alternative antibacterial copper clusters (CuCs) molecule is precisely synthesized utilizing an artificially designed theanine peptide. The prepared CuCs exhibit excellent broad‐spectrum antibacterial activity in vitro, including gram‐positive bacteria (methicillin‐resistant Staphylococcus aureus [MRSA], Staphylococcus aureus, and Staphylococcus epidermidis ) and gram‐negative bacteria ( Escherichia coli and Pseudomonas aeruginosa ). The robust antibacterial effect is due to its ability to not only destroy the bacterial wall structure, but also regulate the ratio of GSH/GSSG by inhibiting the activity of glutathione reductase, thus causing the outbreak of reactive oxygen species and ultimately leading to bacterial death. In addition, in vivo studies demonstrate that CuCs can significantly rescue skin wound infections and sepsis in mice caused by MRSA, and has the same therapeutic efficacy as mupirocin ointment and first‐line clinically anchored anti‐MRSA drug vancomycin. Moreover, CuCs exhibit extremely low cytotoxicity to normal mammalian cells compared to silver and platinum clusters. With further development and optimization, CuCs has great potential as a new class of antibacterial agents to fight antibiotic‐resistant pathogens. Abstract : An effective antibacterial copper clusters (CuCs) molecule is constructed using theanine peptides. The CuCs exhibit good biocompatibility and antibacterial activity by inhibiting the enzymatic activity of glutathione reductase and destroying the bacterial wall structure. In addition, in vivo experiments demonstrate that the CuCs significantly rescued skin wound infections and sepsis in mice caused by MRSA.